Reforms in local politics in ecuador around the crime offemicide - Briones Valverde, Patricia Stephania (Revista Universidad de Guayaquil, 2022)
The main objective of this research has focused on determining the classification of femicide in Ecuador, considering the relevance of international conventions on women's rights in 2020, which allows proposing new reforms for the prevention and eradication of this type of crime. It also sought to identify the constitutive dimensions that intervene in the Ecuadorian legislation on femicide, including the legal and political controversies whose classification has generated, from social constructivism, determining if judicial processes for femicide developed in Ecuador are consistent with the proposals and commitments included in the international conventions on the rights of women. Each of the aspects included in this study was based on the paradigm of social constructivism, based on the legal construction that encompasses national legislation, analyzing the opinion of various experts in this area, which allowed us to delve into the problem of femicide from its classification and penalization. The results allowed to conclude that despite the classification of this crime in Ecuadorian legislation and the provisions established by international treaties, the issue of femicide in Ecuador continues to be a problem that results in effective State action.
Keywords: Femicide; Ecuadorian Criminal Legislation; International Conventions